2021
DOI: 10.1021/acs.macromol.1c01766
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Precursor Strategy Toward the Precise Synthesis of Uniform Hairy Carbon Dots with Tunable Sizes and Size Effects over Their Fluorescence

Abstract: A polymeric precursor strategy was developed toward precise synthesis of uniform and size-tunable hairy fluorescent carbon dots (C-dots, CDs). The strategy was achieved by (i) the synthesis of core−shell 6-arm starlike block copolymers of PGMA-b-PMMA (poly(glucosyl methyacrylate), PGMA; poly-(methyl methacrylate), PMMA), serving as a precursor using atom transfer radical polymerization (ATRP) and (ii) selective carbonization of the inner PGMA chains to generate hairy C-dots with PMMA blocks attaching on the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…17 In our recent work, it was found that FRET effect could happen between different C-dots at high concentrations in addition to FRET pairs formed by sub-fluorophores in a single C-dots. 33 As expected, as the concentration increased gradually until it reached 3.0 mg mL −1 , the fluorescence intensity at λ em = 535 nm began to increase gradually and reached the maximum. In such a range, the concentration did not show any significant effect on the optimal emission wavelength.…”
Section: Polymer Chemistry Papersupporting
confidence: 73%
See 1 more Smart Citation
“…17 In our recent work, it was found that FRET effect could happen between different C-dots at high concentrations in addition to FRET pairs formed by sub-fluorophores in a single C-dots. 33 As expected, as the concentration increased gradually until it reached 3.0 mg mL −1 , the fluorescence intensity at λ em = 535 nm began to increase gradually and reached the maximum. In such a range, the concentration did not show any significant effect on the optimal emission wavelength.…”
Section: Polymer Chemistry Papersupporting
confidence: 73%
“…The sizes of C-dots were easily controlled by molecular weight of inner block in the polymer precursor. 33 In this strategy, 6-arm star-like diblock copolymers with a pendent glucosyl group in the inner block were pre-synthesized and the star-like copolymers were one-to-one transformed into C-dots by carbonizing the glucosyl group.…”
Section: Introductionmentioning
confidence: 99%
“…The core–shell polymer can be used as an ideal nanoreactor for the synthesis of inorganic nanomaterials with uniform and adjustable structure. 258 The nanospace of molecular sieves provides an ideal rigid microenvironment for the growth of CDs, thus leading to uniform size. 259 Similarly, the significant difference in carbonization temperature between metal–organic framework (MOF) and glucose (precursor) is used to realize the composite of CDs and MOF.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the emission wavelength shifted from blue to red when increasing the size of the carbon dots from small to large. 275 Liu et al described the size-dependent fluorescence of carbon dots. The team showed that increasing the size of the carbon dots resulted in red-shifted fluorescence.…”
Section: Optical Properties Of Red-emitting Cnmsmentioning
confidence: 99%